The Armory Show 2006 : International fair of new art, New York City. (New York : Armory Show New York, 2006)
Abramovic, Marina ; Ahearn, John ; Allora & Calzadilla ; Almarcegui, Lara ; Amorales, Carlos ; Aoki, Ryoko ; Applebroog, Ida ; Arsham, Daniel ; Artschwager, Richard ; assume vivid astro focus ; Avotins, Janis ; Baer, Monika ; Baker, Kristin ; Baselitz, Georg ; Baudart, Eric ; Beer, Tjorg Douglas ; Blake, Jeremy ; Blanc, Jean-Luc ; Borremans, Michaël ; Braden, Tim ; Brown, Glenn ; Bul, Lee ; Burns, Ian ; Burr, Tom ; Caivano, Ernesto ; Celmins, Vija ; Chaimowicz, Marc Camille ; Chun, Kwang-Young ; Collins, Andy ; Cotton, Will ; Courtillot, Delphine ; Crow, Rosson ; Daniels, William ; Davis, Tim ; Delbecq, Marcelline ; Demmerle, Yannick ; Dibenedetto, Steve ; Dodiya, Atul ; Doyle Hancock, Trenton ; Eerdekens, Fred ; Emin, Tracey ; Ezawa, Kota ; Fairhurst, Angus ; Fischli & Weiss ; Fletcher, Saul ; Fleury, Sylvie ; Floyer, Ceal ; Francis-Gray, Kevin ; Frecon, Suzan ; Frize, Bernard ; Gillick, Liam ; Gualdoni, Angelina ; Halpern, Emilie ; Hashimoto, Jacob ; Hawkins, Richard ; Hebert, Todd ; Hein, Jeppe ; Henneken, Uwe ; Henning, Anton ; Hernández-Diez, José Antonio ; Herrero, Gustavo ; Hirst, Damien ; Hofer, Andreas ; Horne, Pip ; Houseago, Thomas ; Houshiary, Shirazeh ; Isaeus-Berlin, Meta ; Isenstein, Jamie ; Jackson, Richard ; Jezyk, Enrique ; Johanson, Chris ; Johnson, Matt ; Jungen, Brian ; Katz, Alex ; Kelley, Mike ; Krawen, Hendrik ; Krebber, Michael ; Kusama Yayoi ; Laderman Ukeles, Mierle ; Leonard, Zoe ; Liden, Hanna ; Linzy, Kalup ; Löffelhardt, Stefan ; Maciejowski, Marcin ; Mangold, Robert ; Marden, Brice ; Martin, Bernhard ; McCoy, Jennifer & Kevin ; McDermott & McGough ; Mik, Aernout ; Miller, John ; Moerman, Jean-Luc ; Morris, Rebecca ; Morrison, James ; Murata, Yuko ; Mutu, Wangechi ; Nobel, Jonas ; O'Connor, John ; van Ofen, Michael ; etc.
The Armory Show 2006 : International fair of new art, Piers, New York, 2006-03-10. 2006-03-13
boek